Subsonic wind tunnels in thermo-fluid research - Aarnio, Onni (My University, 2025)
This thesis looks at the design and applications of subsonic wind tunnels in thermo-fluid research. The components of the subsonic wind tunnel and measurement methods are analyzed. This thesis also covers the applications of subsonic wind tunnels in aerodynamics, heat transfer and academia. Challenges regarding energy consumption and scaling effects are analyzed with recommendations for future development.
Keywords: wind tunnel, subsonic, fluid mechanics, thermodynamics, sensor